Exogenous Nicotinamide Adenine Dinucleotide Induces Resistance to Citrus Canker in Citrus - Alferez, Fernando M.; Gerberich, Kayla M.; Li, Jian-Liang; Zhang, Yanping; Graham, James H.; Mou, Zhonglin (Frontiers in Plant Science, 2018)
Nicotinamide adenine dinucleotide (NAD) is a universal electron carrier that participates in important intracellular metabolic reactions and signaling events. Interestingly, emerging evidence in animals indicates that cellular NAD can be actively or passively released into the extracellular space, where it is processed or perceived by ectoenzymes or cell-surface receptors. We have recently shown in Arabidopsis that exogenous NAD induces immune responses, that pathogen infection causes leakage of NAD into the extracellular fluid at concentrations sufficient to induce immune responses, and that removal of extracellular NAD (eNAD) by expressing the human NAD-metabolizing ectoenzyme CD38 partially compromises plant immunity. We therefore hypothesize that, during plant-microbe interactions, NAD is released from dead or dying cells into the extracellular space where it interacts with adjacent naïve cells’ surface receptors, which in turn activate downstream immune signaling. However, it is currently unclear whether eNAD signaling is specific for Arabidopsis or the Brassicaceae family. In this study, we treated citrus plants with exogenous NAD and tested NAD-induced transcriptional changes and disease resistance. Our results show that NAD induces profound transcriptome changes and strong resistance to citrus canker, a serious citrus disease caused by the bacterial pathogen Xanthomonas citri subsp. citri (Xcc). Furthermore, NAD-induced resistance persists in new flushes emerging after removal of the tissues previously treated with NAD. Finally, NAD treatment primes citrus tissues, resulting in a faster and stronger induction of multiple salicylic acid pathway genes upon subsequent Xcc infection. Taken together, these results support that eNAD is a conserved damage-associated molecular pattern in plants.